Immunohistochemical study of T-lymphocytes in the skin of patients with psoriasis vulgaris - Kutasevych , Ya.F.; Kondakova , H.K.; Goidenko , N.I. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. An in-depth study of the immunohistochemical features of inflammatory processes in the morphological elements of the psoriatic skin rash is important in terms of obtaining the latest data on the pathogenesis of psoriasis. Objective. To determine the content of CD3+-, CD4+-, CD8+- lymphocytes in skin biopsies of patients with psoriasis vulgaris during the exacerbation of the disease. Methods. Immunohistochemical study of biopsy material is undertaken from areas to the skin psoriasis pouring out at 5 patients on psoriasis. The row of immunogistochemikal methodologies was used also for the exposure of expression of CD3,CD4, CD8. Results. The conducted study showed that the exacerbation of psoriasis vulgaris is characterized by an increase in the focus of inflammation of the cells of the lymphocytic row. The most represented cell type is CD4+, CD8+ with a predominance of CD8-positive cells. Conclusion. An inflammatory process in a skin at psoriasis develops as a result immunopathologich reactions. Most presented is a cellular link – CD4, CD8